A framework for optimization of energy efficiency and integration of hybridized-solar energy in agro-industrial plants: Bioethanol production from cassava in Ghana - Amo-Aidoo, A.; Hensel, O.; Korese, J.K. (Energy Reports, 2021)
This study presents a methodological framework for auditing, optimization as well as the integration of hybridized solar energy in Ghana’s agro-industrial sector. The Functional Analysis System Technique was introduced for systematically translating plant-wide energy requirements into detailed functional and performance design criteria for energy efficiency, optimization, and solar energy integration. The results of the case study indicated that insulating the fermenter and distiller as well as using energyefficient rasper, pumps and cables reduced energy consumption by 41.8%. The cost of integrating solar thermal energy was 31.8% higher than solar photovoltaic power due to a lack of subsidies in the sector. A 250 kW solar photovoltaic model was designed with a performance ratio of 75% and a solar hot water system with a thermal fraction of 91% for electricity and process water respectively. The framework, therefore, presents an invaluable tool for optimizing energy efficiency and integrating solar thermal and solar photovoltaic energy sources for the agro-industrial sector
Keywords: Framework; Energy optimization; Solar energy integration; ACE: Water, Irrigation and Sustainable Agriculture; Ghana; Water & irrigation; University of Development Studies